The study of heat transfer enhancement of solar air heater using airfoiled extended surface - Liew, Minzhao (Universiti Teknologi PETRONAS, 2017)
Over the last decades, solar air heaters (SAHs) are widely use all around the world. It is recognized as one of the most popular solar energy utilization system which uses fundamental of heat transfer to collect and convert solar energy to heat energy for air, space, working fluid and more. Solar energy from the Sun is collected by this device through a surface which is called absorber plate through convection and radiation, the energy is then transferred to the working fluid or space by using convection and radiation. Although solar air heaters using nowadays are performing well and fine, there is still room for further improvement on its performance and efficiency.